Body image perception and social support are important predictors of quality of life in bladder cancer patients after cystectomy with urinary diversion - Carl, Nicolas; Schmidt, Leah; Büdenbender, Björn; Blum, Anja K.; Nientiedt, Malin; Alpers, Georg W.; Kriegmair, Maximilian; Grüne, Britta (Urologia internationalis, 2024)
Introduction: Systematic evaluations focusing on the perception of body image and social support in relation to quality of life (QoL) outcomes in patients radical cystectomy (RC) with urinary diversion (UD) are currently lacking. This study investigated the relationship between body image perception, social support, and QoL in bladder cancer patients who underwent RC with UD. Methods: A cross-sectional survey was conducted using validated general oncology tools to assess QoL in relation to newly implemented tools assessing body image perception and social support. Body image perception was assessed with the Self-Image Scale, and social support was assessed using the Illness-Specific Social Support Scale. Logistic regression models were used to analyze factors associated with QoL and body image, respectively. Results: The survey revealed a significant association of body image perception with QoL, as well as social support with body image perception. This is the first study to systematically evaluate these psychosocial factors in the context of QoL for RC patients, highlighting their critical role in patient-reported outcomes. Conclusion: Body image perception and social support are important psychosociological factors that affect QoL of bladder cancer patients post-RC. Targeted psychosocial interventions could be promising for improving QoL patients post-RC.
Online veröffentlicht: 30. August 2024
Gesehen am 04.11.2024